Identification of Body Image Problem: Implications for Promoting Body Image Resilience in Female College Students - Cicilia Larasati Rembulan; Andrian Liem (Laboratory of General Psychology, Faculty of Psychology, Universitas Surabaya, 2014)
The aim of this study was to describe and identify body image problems in non-clinical female university students in Surabaya. Participants were female university students (N = 143) aged 18 to 21 years old, obtained through purposive sampling. This survey used Likert type scale (2 scales) and a pictorial scale as the research instruments. The data collected were analyzed with descriptive statistics and cross tabulation of demographic questionnaire. The results showed that there was a gap between the desired body perception and the real one. The prominent behavior was compulsive behavior. Body image problems, which comprised of body image dissatisfaction, cognitive distortion, and body image compulsive behavior were also experienced by some young women in normal population even when their body mass index were normal.